Konsekuensi Produk Penanaman Emas Dengan Perjanjian Murabahah Terhadap Kemakmuran Konsumen - Diana Farid; Muhammad Husni Abdulah Pakarti; Iffah Fathiah; Hendriana Hendriana; Ade Jamarudin (Jurnal Ilmiah Ekonomi Islam, 2023)
This study aims to determine how the gold murabahah investment product and customer welfare, as well as to determine how the effect of gold murabahah investment product on the welfare of customers at PT. Abadi Optimization Gold Bandung City Branch. The factors tested in this study were the gold murabahah investment product as the independent variable. While the welfare of customers as the dependent variable. The research method used in this research is verification method. The population in this study were customers of PT. Optima Eternal Gold as many as 100 people. The sampling technique used in this study is a non-probability sampling technique with a saturated sampling method, while to calculate the sample size using the slovin formula, so that the sample in this study is 100 customers of PT. Eternal Optima Gold. The analytical method used in this study is simple linear regression analysis at a significance level of 5%. The program used in analyzing the data uses the Statistical Package for Social Sciences (SPSS) Ver.19.00. Based on the results of the partial and simultaneous research, it shows that the gold murabahah investment product has an effect on the welfare of customers at PT. Abadi Optimization Gold Bandung City Branch. In addition, the magnitude of the influence of the gold murabahah investment product in contributing to the customer's welfare is 54.0%.